Development Of Decision Support System For Scheduling Machine Loading By Using Microsoft Office - Khiew, Fook Yun (Universiti Sains Malaysia, 2018)
Manufacturing industry will receive a large amount of customer orders according to its capacity to achieve enough business profit, so order scheduling is important to assign the production orders to various work stations in the plant. In fact, the existing file of Excel will contain clusters of data stored and the clusters of data are required to be managed orderly and this will cause to a failure for Excel to update new information which cause the industry to face problems. Therefore, Microsoft Access is introduced to use with Microsoft Excel because both tools are essential to be practised for managing the customer order data. The aim of this design project is to create a template for storing data and scheduling the machine loading by using Microsoft Access with assist of Microsoft Excel. By using Microsoft Access, database is created and used as a storage for the company to keep updating the new information since the records are free in database and kept unchanged overtime. Moreover, using Excel in this design made it easy to perform numerical calculations, format cells, and adjust layouts to generate the output for sequencing machine loadings. Priority rules such as Earliest Due Date (EDD) and Shortest Processing Time (SPT) were used for sequencing the jobs. In general, the SPT priority rule pushes most loads through the system to completion more quickly than will the EDD rule. Speed can be an advantage, but only if loads can be delivered sooner than promised and revenue collected earlier. However, EDD rule can manage the jobs to be completed on time. All the results are the reference for the company to do decision making according its competitive priorities.